How and on whom to perform uterine-preserving surgery for uterine prolapse - Sumin Oh; Myung Jae Jeon (Korean Society of Obstetrics and Gynecology, 2022)
The demand for uterine preservation in pelvic reconstructive surgery for uterovaginal prolapse is steadily increasing, and several procedures have been introduced, such as sacrospinous hysteropexy, uterosacral hysteropexy, sacrohysteropexy, and hysteropectopexy. However, the benefits and risks of uterine-preserving surgeries are not well understood. This review discusses the current evidence surrounding uterine-preserving surgery for uterovaginal prolapse repair. This may help surgeons and patients have a balanced discussion on how and on whom to perform uterine-preserving surgery.